Ensino religioso, representações sociais e formação docente: implicações sobre o processo de atuação do professor de ensino religioso - Firmino, Girleine de Mélo Andrade (2012)
We discuss about the social representations about teacher education and its importance to a healthy practice in religious education, directly influencing the stance taken by their teachers, and thus reaching the worldview of the students with whom they relate. We seek to start reporting the historical trajectory of Religious Education and the various changes over time in relation to the concept of Teacher Education, following the challenges relevant to teachers of Religious Education, seeking to know them through the Social Representations, understanding how the same in spite of dealing directly with common sense socially constructed, reveal the possible intentions we have about our stance against the religious education teacher and our degree of involvement in it.